The Psychiatry Information Card: a pocket resource to assist students’ transition into psychiatry clerkship (Canadian Medical Education Journal, 2024)
Implication StatementThe Psychiatry Information Card (PIC) offers a practical, structured concise resource to enhance medical students' confidence, knowledge, and self-reflection during psychiatry rotations. Its utility lies in providing targeted support for students navigating the transition from classroom learning to clinical practice, and addressing specific challenges encountered during this critical phase of medical education. By offering accessible and relevant information aligned with rotation objectives, the PIC increased knowledge pre and post rotation, and enhanced the learning experience. The PIC's acceptability is demonstrated by the high recommendation rate (90%) among participants, who endorsed its integration into the rotations. Additionally, the low cost and ease of distribution make the PIC a cost-effective resource, further supporting its feasibility for widespread implementation. Therefore, we recommend formal integration into the curriculum.